Bioengineered SMaRT Human Neural Stem Cells to Degrade Scar and Enhance Regeneration in Chronic Spinal Cord Injury. (16th November 2020) - Ahuja, Christopher S; Khazaei, Mohamad; Hong, James; Senthilnathan, Vjura; Hasan, Ali; Dadabhoy, Maryam; Gulati, Nitya; Aiyar, Niharikaa; Punjani, Nayaab; Walji, Inaara; Toossi, Amirali; Fehlings, Michael G
Abstract: INTRODUCTION: Translationally-relevant human induced pluripotent stem cell-derived neural stem cells (hiPS-NSC) are an exciting regenerative approach for traumatic spinal cord injury (SCI). Unfortunately, most individuals are in the chronic phase of their injury where dense perilesional chondroitin sulfate proteoglycan (CSPG) scarring significantly impairs regeneration. Scar-modifying enzymes can enhance recovery, however, intrathecal catheter injection increases the risk of off-target CNS effects. METHODS: A proprietary scar-degrading enzyme was genetically integrated into hiPS-NSCs under an inducible promoter using CRISPR-Cas9. Enzyme expression was extensively characterized in vitro by biochemical and culture assays. To assess efficacy in vivo, T-cell deficient rats with chronic C6-7 contusion-compression injuries were randomized to receive (1) NSCs, (2) SMaRT enzyme-expressing NSCs (activated), (3) SMaRT NSCs (not activated), or (4) vehicle control. Animals were assessed with biweekly neurobehavioural tests of locomotion, forelimb recovery, and sensation through 22-weeks post-injury. A subset underwent high-throughput single-cell sequencing(scRNAseq). RESULTS: SMaRT cells express the enzyme and reporter. SMaRT cells retain key human NSC characteristics including the capacity to spontaneously form neurospheres and differentiate along key neuroglial lineages. SMaRT cells degrade CSPGs in vitro and allows GFP + human NSCs to extend into CSPG-dense scar-like areas in vitro . Conditioned SMaRT cell media also rapidly degrades in situ rodent CSPGs in ex vivo injured spinal cord cryosections. Activated SMaRT cells significantly improve forelimb grip strength (751 ± 58vs404 ± 55 g vehicle; P < . 01). Grafted human cells are also extending remarkably long (cervicomedullary junction to mid-thoracic) axons through rodent white matter. Lineage tracing shows that grafts can extend across the injury site. Numerous human cells stain for mature neuron marker, NF200, and growth associated protein, GAP43, suggestive of active axonal growth long after transplant. Grafted cells also demonstrate differentiation to oligodendrocytes. Preliminary scRNAseq results suggest that SMaRT oligodendrocytes express higher levels of myelin-assembly protein, annilin, and SMaRT neurons express higher galectin-3, an axon pathfinding protein. CONCLUSION: This work provides exciting evidence that genetically-engineered SMaRT cells can successfully degrade CSPG scar and that human NSC grafts can form long axonal processes in the typically inhibitory chronic cervical SCI niche.